Engine Performance and Exhaust Emission Characteristics of Fuel Oil-Diesel Fuel Mixture in a Single Cylinder Engine - Mohd Shah Rizal Bin Mohd Yusof, Mohd Shah Rizal (Universiti Teknologi Petronas, 2008)
The experimental results show that the engine power and torque are lower than the value obtained from Diesel fuel. As for exhaust emission, adding MFO do increase CO emission and particulate matter, but reduce the NOx emission. It is proven that medium fuel oil can be used as an alternative fuel for diesel engine, with some lose of the engine performance and emission characteristics.